The Praxis of Horse Riding: An Autoethnographic Study - Zetterqvist Blokhuis, Mari (Humanimalia, 2018)
In an autoethnographic approach, theories of practical knowledge were used to explore the praxis of riding and to describe, interpret, and analyze the interspecies relation between rider and horse during riding. Both rider and horse are embodied subjects taking part in an active process of “becoming with”, and as a result of the interaction, both parts change and adapt to each other resulting in a shared practical knowledge. To build a trustful relation during riding, the rider’s as well as the horse’s emotions and feelings need to be taken into account. It is suggested that there are two kinds of “equestrian feel”, one connected to the rider’s body feeling of the horse through his/her body while the other is an “inner” equestrian feel when rider and horse move as one body, like a centaur. The latter could be seen as an expression of phronesis since it is guided by what is good for the human (and hopefully the horse) in itself rather than aiming at a specific outcome.